2014
DOI: 10.3233/sw-140158
|View full text |Cite
|
Sign up to set email alerts
|

Semantic technologies for historical research: A survey

Abstract: Abstract. The diversity of sources of information for historical research fill a continuum between individual accounts transmitted for instance in letters but also in poems and songs, and aggregated statistical information as in the case of historical census. Historiography shares this heterogeneity and complexity of source material with other humanities fields. Methods to order this rich material, and by this ordering also to determine the way history is told are as old as history writing and vary among the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 44 publications
0
56
0
1
Order By: Relevance
“…In the last years, there is a remarkable interest in the application of Semantic Web technologies to history research both by Semantic Web researchers and historians, as documented by the survey reported in (Meroño-Peñuela et al, 2014). Many results considered in such a survey show the effectiveness of semantic formalisms (including ontologies), Linked Data best practices and NLP approaches in publishing and connecting historical datasets and in enhancing search, retrieval and classification.…”
Section: Other Interesting Work To Be Taken Into Accountmentioning
confidence: 96%
“…In the last years, there is a remarkable interest in the application of Semantic Web technologies to history research both by Semantic Web researchers and historians, as documented by the survey reported in (Meroño-Peñuela et al, 2014). Many results considered in such a survey show the effectiveness of semantic formalisms (including ontologies), Linked Data best practices and NLP approaches in publishing and connecting historical datasets and in enhancing search, retrieval and classification.…”
Section: Other Interesting Work To Be Taken Into Accountmentioning
confidence: 96%
“…It is not difficult to see the benefits of publishing historical sources as Linked Open Data [7]. However, it is unclear whether standard Linked Data modeling and publication pipelines are suitable for historical sources.…”
Section: Historical Sources As Rdf Graphsmentioning
confidence: 99%
“…Historical research has steadily been adopting semantic technologies [1], [2], [3] to tackle several recent problems in the field, such as making explicit the semantics contained in the historical sources, formalising them and linking them [4]. Historians, especially in Digital Humanities, are starting to use historical sources to aggregate information about history.…”
Section: Introductionmentioning
confidence: 99%